Molecular Identification and Diversity of Yeasts Associated with Apis cerana Foraging on Flowers of Jatropha integerrima - ADI BASUKRIADI; WELLYZAR SJAMSURIDZAL; BANGGA BERISTAMA PUTRA (Indonesian Society for microbiology, 2010)
There are only a few reports from tropical countries, and none from Indonesia, on yeasts associated with the Asiatic honeybee, Apis cerana. Here we report on yeasts associated with A. cerana foraging on flowers of Jatropha integerrima in the campus of the Universitas Indonesia, Depok, Indonesia. Yeasts were isolated from guts of 30 individual pollen-collecting bees (PCB) and nectar-collecting bees (NCB), and identified by their internal transcribed spacer (ITS) regions of their rDNA sequences. Based on ITS regions sequence data, 14 representative yeast isolates obtained from A. cerana were found to be closely related to Aureobasidium pullulans, Dothioraceae sp., Candida cf. apicola, C. cf. azyma, C. cellae, Metschnikowia sp., Kodamaea ohmeri and Yarrowia lipolytica. Undescribed yeast of the genus of Metschnikowia was also discovered in this study. At present, we assume there is association between C. cf. apicola and species closely related to C. cellae with A. cerana. Yeasts species associated with PCB differ from those found in NCB, indicating that PCB and NCB possess different and specific yeasts communities. Some yeasts species isolated from A. cerana show a low degree of similarity to their closest related species. Our study sheds light on the detection of several new taxa of yeasts associated with A. cerana.